DOI: 10.29007/16q5
|View full text |Cite
|
Sign up to set email alerts
|

Analyzable Legal Yes/No Question Answering System using Linguistic Structures

Abstract: A central issue of yes/no question answering is usage of knowledge source given a question. While yes/no question answering has been studied for a long time, legal yes/no question answering largely differs from other domains. The most distinguishing characteristic is that legal issues require precise linguistic analysis such as predicates, case-roles, conditions, etc. We have developed a yes/no question answer-ing system for answering questions in a legal domain. Our system uses linguistic analysis, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Legal question answering has been the focal point of many studies. Early systems adopted rules and other unsupervised techniques for answering Yes/No questions from bar exams [66], [67]. Later works are generally supervised, using classical machine learning methods (e.g., logistic regression) [68] and different types of neural networks (e.g., CNN) [69], [70].…”
Section: A An Overview Of Major Legal Nlp Tasksmentioning
confidence: 99%
“…Legal question answering has been the focal point of many studies. Early systems adopted rules and other unsupervised techniques for answering Yes/No questions from bar exams [66], [67]. Later works are generally supervised, using classical machine learning methods (e.g., logistic regression) [68] and different types of neural networks (e.g., CNN) [69], [70].…”
Section: A An Overview Of Major Legal Nlp Tasksmentioning
confidence: 99%
“…Kano (2016) suggested a penalized scoring method assigning scores to parts of documents that include terms, which indicate that the answer is no. Kano, Hoshino, and Taniguchi (2017) built a system using linguistic analysis to find correspondences of predicates and arguments from the given problem sentences and knowledge source sentences. Although these approaches are interpretable, the experience has shown that more complex systems are necessary for solving the QA problem, while the machine learning approaches are necessary for generalization purposes.…”
Section: Related Workmentioning
confidence: 99%
“…Works based on this approach, such as (Kim et al, 2013) have developed different approaches to answer yes/no questions relevant to civil laws in legal bar exams. A bar examination is intended Work Approach (Kim et al, 2013) Antonym detection and Semantic Analysis (Kim et al, 2014) TF-IDF, LDA and SVM (Kim et al, 2016) Paraphrasing detection (Taniguchi & Kano, 2016) Case-role analysis (Kano et al, 2017) Using linguistic structures (Taniguchi et al, 2018) Using Framenet to determine whether a candidate is qualified to practice law in a given jurisdiction. There is a recurring concern in the literature on whether it is possible to pass this type of test without human supervision.…”
Section: Yes/no Answersmentioning
confidence: 99%
“…Other authors (Taniguchi & Kano, 2016;Taniguchi et al, 2018) has addressed the problem by case-role analysis and Framenet 5 , respectively. Finally, Kano et al has explored, for the first time, linguistic structures (Kano et al, 2017). Table 3 summarizes all these works.…”
Section: Yes/no Answersmentioning
confidence: 99%